The evaluation of turmeric (Curcuma longa) supplementation within feed as an antioxidant towards growth performance of catfish Clarias gariepinus Burchell 1822 in zero water exchange condition - Thoy Batun Citra Rahmadani; Dedi Jusadi; Mia Setiawati; Yuni Puji Hastuti (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2020)
The objective of this research was to evaluate the supplementation of turmeric in the diet on antioxidant status and growth performance of African catfish (Clarias gariepinus) in zero water exchange condition. This study used a completely randomized design with 4 treatments and 4 replications. Each treatment consisted of feed supplementation turmeric at dosage of 0; 2.5; 5 or 7.5 g kg-1 diet. One hundred catfish juvenile (5.95±0.05 g) were stocked in intermediate bulk container (IBC) tank (1×1×1 m3) and rearing in zero water exchange condition for 60 days. Catfish were fed at satiation twice a day, in the morning and evening. The results showed that an increase in antioxidant content in catfish fed with the addition of turmeric, which simultaneously also reduced the percentage of liver damage. The parameters of liver damage can be seen from several parameters i.e. pale liver, droplet fat and fat content in the addition of turmeric treatment is lower than without the addition of turmeric. However, catfish fed with the addition of turmeric did not show significant results in terms of growth performances. Abstrak Tujuan penelitian ini adalah untuk mengevaluasi penambahan kunyit ke dalam pakan sebagai antioksidan dan kinerja pertumbuhan ikan lele Afrika (Clarias gariepinus). Penelitian ini menggunakan rancangan acak lengkap dengan 4 perlakuan dan 4 ulangan. Setiap perlakuan terdiri atas penambahan dosis kunyit sebanyak 0; 2,5; 5 dan 7,5 g kg-1 pakan. Seratus benih ikan lele (5,95±0,05 g) dipelihara dalam tangki Intermediate Bulk Container (IBC) (1×1×1 m3) dan dipelihara tanpa pergantian air selama 60 hari. Ikan lele diberi pakan secara at satiation dua kali sehari. Hasil penelitian menunjukkan bahwa terjadi peningkatan kandungan antioksidan pada ikan lele yang diberi pakan dengan penambahan kunyit di dalamnya, yang secara bersamaan juga mengurangi persentase kerusakan hati. Parameter kerusakan hati dapat dilihat dari beberapa parameter, seperti hati pucat, droplet lemak dan kandungan lemak pada perlakuan penambahan kunyit lebih rendah dibandingkan tanpa penambahan kunyit. Namun ikan lele yang diberikan pakan dengan penambahan kunyit tidak menunjukkan hasil yang signifikan dari segi pertumbuhannya.